ANALISIS KONSEPTUAL: ZAKAT DAN PAJAK SEBAGAI INSTRUMEN KEADILAN SOSIAL DALAM SISTEM EKONOMI INDONESIA - Fadla Nurul Khiar; Eko Ribawati (CV. Denasya Smart Publisher, 2026)
Zakat and tax are two financial instruments that play an important role in realising social justice and economic welfare in Indonesia. This study aims to analyse the position, similarities, differences, and potential synergies between zakat and tax in the Indonesian economic system. This study uses a descriptive qualitative method with a literature study approach sourced from scientific journals, books, and related regulations. The analysis was conducted conceptually based on a literature study to examine the theoretical relationship between zakat and tax as instruments of social justice in the Indonesian economic system. The results of the study show that zakat and tax have the same function in wealth redistribution, although they differ in their legal basis and implementation mechanisms. The integration of the two through the zakat tax deduction policy has the potential to strengthen the national fiscal system and encourage the creation of sustainable social justice. This article contributes to enriching Islamic economic studies by offering a conceptual framework for the synergy between zakat and tax as instruments of equitable fiscal policy in Indonesia.